Weaving a Family and a Nation Through Two Latvian Looms. Issue 2 (4th May 2018) - Schamberger, Karen
Abstract: This article demonstrates the ways in which some post-Second World War Latvian refugees maintained a sense of 'cultural nationalism' across two generations. Using object biography, I interweave the stories of the Apinis family and two weaving looms created in German Displaced Persons camps after the Second World War that are now in the collections of Museum Victoria and the Latvians Abroad: Museum and Research Centre. When the Australian-born daughter 'returned' to her parent's homeland, she was forced to confront the gap between her family's memories and the memories of people who had remained in Latvia after the war.